Analisis Pengaruh Iklan, Kepercayaan Merek, dan Citra Merek terhadap Minat Beli Konsumen - Arista, Desi; Astuti, Sri Rahayu Tri (Jurnal Ilmiah Aset, 2011)
Globalization era makes information and technologies increase very fast and can be known quickly. One of information technology is the Interconnected Network, or more popular as the Internet. Therefore, to satisfy consumers PT. Telkom issued a product called Speedy. Many factors influence customers before purchasing a product consumers. The purpose of this study is to determine the influence of advertising, brand trust and brand image to the buying interest. Brand trust is the highest independent variable that influences the dependent variable (buying interest) then advertising and lastly the brand image.